Impact of an aerosolized or intramuscular adenovirus type 5-vectored COVID-19 vaccine on Fc-mediated immune effector functions in a hybrid immunity population - Gan, Mingzhi; Han, Weiwei; Li, Chuang; Li, Simin; Huang, Zhuangzhuang; Xu, Lingjie; Xu, Xiaoyu; Zhai, Xiangjun; Chen, Yuxin; Li, Jingxin (Frontiers in Immunology, 2025)
BackgroundBeyond the role of neutralizing antibodies in protecting against SARS-CoV-2, Fc-mediated antibodies functions may offer additional immune defense. This study aimed to evaluate the Fc-mediated immune responses elicited by aerosolized and intramuscular Ad5-nCoV vaccines in a Chinese population with hybrid immunity.MethodsSerum samples were collected from the immunogenicity sub-cohort within a multicenter, partially randomized platform trial comparing aerosolized and intramuscular adenovirus type 5-vectored COVID-19 vaccine (Ad5-nCoV) boosters in adults in China. Participants were enrolled approximately six months after an Omicron wave in late 2022, and randomized to receive a booster dose with aerosolized or intramuscular Ad5-nCoV. Fc-mediated immune responses to wild-type and XBB.1.16 variant spike proteins were assessed by measuring antibody-dependent cellular phagocytosis (ADCP), antibody-dependent neutrophil phagocytosis (ADNP), and antibody-dependent cellular cytotoxicity (ADCC) before vaccination, and at 14 days, 3 months, 6 months post-booster. Correlations between Fc-mediated responses (ADCP, ADNP, ADCC) and neutralizing antibodies, IgG, and IgA levels responses were also analyzed.ResultsIntramuscular Ad5-nCoV vaccination significantly induced Fc-mediated effector functions against wild-type spike protein, with peak responses at 14 days post-booster, including ADCP score of 107.21 (95% CI: 84.43-129.99), ADNP score of 133.96 (95% CI: 112.81-155.11), and ADCC fold induction of 9.64 (95% CI: 8.57-10.70). These responses gradually waned over time. In contrast, aerosolized Ad5-nCoV did not significantly enhance ADCP or ADNP, but did elicit notable ADCC responses, peaking at 3 months post-vaccination (fold induction: 7.85,95% CI: 6.66-9.04). Fc-mediated responses to XBB.1.16 were lower than those to the wild-type spike. Notably, the fold reductions in ADCP, ADNP, and ADCC against XBB.1.16 were less pronounced than the corresponding reduction in neutralizing antibody titers.ConclusionsIntramuscular Ad5-nCoV vaccination elicited robust ADCP, ADNP, and ADCC responses, while the aerosolized formulation primarily induced ADCC activity. Fc-mediated effector functions exhibited greater cross-reactivity against emerging variants compared to neutralizing antibodies, but correlated only weakly with neutralizing antibody titers.